2022
DOI: 10.21608/znj.2022.269324
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Mothers Regarding First aids of Home Injuries Among Preschool Children

Abstract: Background: Mother's knowledge and practice related to safety measures taken at home environment to prevent home injuries are important in reducing incidence of injuries as many adverse consequences of injuries can be averted if mothers know what actions to be taken. Aim of the study:The aim of the present study was to assess knowledge and practice of mother's regarding home injuries among preschool children. Subjects and method: Research design: A cross-sectional descriptive design was used to conduct the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In Africa, studies conducted in Egypt showed that mothers' knowledge of first-aid practices regarding domestic accidents is also low. The study conducted by Gouda et al [9] revealed that 90.5% of mothers had unsatisfactory knowledge about home injuries in Egypt, and another study in Egypt showed that two-fifths of the mothers participating had fair knowledge regarding first-aid [10]. Regarding the factors associated with mothers' knowledge, African studies revealed that (i) the mother's age and the mother's education level were statistically significant independent positive predictors of higher knowledge scores [9] in Egypt, (ii) age, education, and occupation were statistically significant independent positive predictors of knowledge scores in Egypt [10], and (iii) that age, area of residence, and the level of education of the participants played a variable role regarding first-aid awareness, attitude, and knowledge in Kinshasa, Democratic Republic of Congo [11] (but this knowledge covered first-aid in general and was not focused on domestic accident in children).…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, studies conducted in Egypt showed that mothers' knowledge of first-aid practices regarding domestic accidents is also low. The study conducted by Gouda et al [9] revealed that 90.5% of mothers had unsatisfactory knowledge about home injuries in Egypt, and another study in Egypt showed that two-fifths of the mothers participating had fair knowledge regarding first-aid [10]. Regarding the factors associated with mothers' knowledge, African studies revealed that (i) the mother's age and the mother's education level were statistically significant independent positive predictors of higher knowledge scores [9] in Egypt, (ii) age, education, and occupation were statistically significant independent positive predictors of knowledge scores in Egypt [10], and (iii) that age, area of residence, and the level of education of the participants played a variable role regarding first-aid awareness, attitude, and knowledge in Kinshasa, Democratic Republic of Congo [11] (but this knowledge covered first-aid in general and was not focused on domestic accident in children).…”
Section: Introductionmentioning
confidence: 99%